1984
DOI: 10.1002/mpo.2950120405
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's disease presenting in epitrochlear nodes

Abstract: Two cases of Hodgkin's Disease (HD) presenting in epitrochlear nodes are described, and compared to four similar cases gleaned from the literature. The nodular sclerosis type of HD was present in 5 of the 6 patients. Of the four patients staged with laparotomy, two had infradiaphragmatic disease. A treatment approach using radiation alone for patients with disease limited to the epitroclear region is presented, and anatomical considerations of the treatment technique are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…We identified 144 articles, of which 79 (including 507 subjects) were found to be eligible for inclusion. [ 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 ] Infections ( n = 356, 70.2%) and neoplasms ( n = 116, 22.9%) were the most common reported cau...…”
Section: Resultsmentioning
confidence: 99%
“…We identified 144 articles, of which 79 (including 507 subjects) were found to be eligible for inclusion. [ 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 ] Infections ( n = 356, 70.2%) and neoplasms ( n = 116, 22.9%) were the most common reported cau...…”
Section: Resultsmentioning
confidence: 99%
“…2 Since then, several others have reported on this rare presentation as either isolated individual cases or part of a larger series of Hodgkin patients (see Table 4). [3][4][5][6][7][8][9][10] Most of these reports provide only limited information on treatment techniques and long term prognosis. In terms of frequency, Kaplan reported on 340 patients treated for Hodgkin disease and found that 3 of the patients presented with epitrochlear lymphadenopathy (1%), 11 data similar to the findings in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our impression, in a large central hospital in sub-Saharan Africa, was that palpable epitrochlear lymph nodes were a good marker of early HIV disease. Osler noted that such nodes were a prominent clinical feature of secondary syphilis,2 but nowadays the palpability of this node is not emphasised 3 4 5. We assessed the value of regional lymph node enlargement, by site and size, as a predictor of HIV disease.…”
mentioning
confidence: 99%